The Potential Implications of the United States-China Trade War on Vietnam: A Review from the Perspective of International Political Economy (2018–2025) - Van Kim Hoang Ha (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
The United States–China trade war (2018–2025) has triggered significant shifts in the global economy, particularly affecting Asian countries. This article analyzes the economic and political implications of the trade war on Vietnam, with a focus on national interests. A descriptive qualitative research method is employed, drawing on literature review and secondary data analysis. Within the framework of international relations theory, the study integrates perspectives from realism (balance of power), complex interdependence, and international political economy to interpret Vietnam’s response. The findings indicate that Vietnam initially benefited from increased exports and inflows of foreign direct investment (FDI) during the early phase of the trade war, but faces long-term risks such as dependency on China-dominated global supply chains and heightened vulnerability to external shocks. In response, Vietnam has pursued market diversification (leveraging various free trade agreements) and adopted a balanced economic diplomacy strategy between major powers. The study recommends strengthening domestic production capacity, developing local resources (raw materials and components), and aligning foreign policy to maintain productive neutrality in order to safeguard Vietnam’s national interests amid this global conflict.